TRADISI FOKOMPA KAMPANA’A DALAM PROSESI PEMINANGAN PADA MASYARAKAT SIOMPU BUTON SELATAN PERSPEKTIF HUKUM ISLAM - M. Miswar Zarah; Lomba Sultan; Muh. Jamal Jamil (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
The main issue of this research is how the implementation of the tradition of "fokompa kampana’a" in the engagement process in the Siompu District community of South Buton Regency from the perspective of Islamic law. This research is qualitative field research using Sharia and sociological approaches. The research results indicate that before the implementation of "fokompa kampana’a," two preliminary steps are taken, namely "posoloi" and "fotibua." The implementation of the tradition of "fokompa kampana’a" is conducted three times. First, "kafe’awutino lambu" as a proposal presentation. Second, "kafendua" is the formal engagement as a marker that both parties are engaged. Third, "woa’ano wua" or the engagement ceremony accompanied by the partial delivery of the dowry according to tradition. In general, the implementation of the tradition of "fokompa kampana’a" does not contradict Islamic law because many aspects align with Islamic teachings. Preserving the tradition of "fokompa kampana’a" as cultural wealth needs to be done while considering Islamic values and simplifying some processes and materials deemed burdensome according to the community's capabilities.